Akademische Plaudereien zur Frauenfrage : Vier rechts- und culturgeschichtliche Vorträge in populärer Form - Wahrmund, Ludwig, 1860-1932 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik ;, 1901)
These four lectures were inspired by the admission of women students to the law faculty at the University of Innsbruck, in which Wahrmund was a professor of law. The lectures are general, dealing with a variety of topics related to women.